2017
DOI: 10.1111/jocn.14051
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malnutrition among older people in medical and surgical wards in hospital and quality of nutritional care: A multicenter, cross‐sectional study

Abstract: These findings will provide indications on the strategies needed to overcome such barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 48 publications
3
32
2
Order By: Relevance
“…In addition, many nurses and some patients described the food as unpalatable. Similar problems have been identified internationally, for example, Bonetti et al (2017), who indicated similar concerns for patients in Italian hospitals. Furthermore, this study highlighted the potential flow-on effects to organisational changes in the way patient foods were stored and distributed; highlighting the need for widespread consultation, right to the point-of-care, prior to such changes being implemented, and then having a strategy to both evaluate and respond to any problems arising from such changes.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, many nurses and some patients described the food as unpalatable. Similar problems have been identified internationally, for example, Bonetti et al (2017), who indicated similar concerns for patients in Italian hospitals. Furthermore, this study highlighted the potential flow-on effects to organisational changes in the way patient foods were stored and distributed; highlighting the need for widespread consultation, right to the point-of-care, prior to such changes being implemented, and then having a strategy to both evaluate and respond to any problems arising from such changes.…”
Section: Discussionsupporting
confidence: 72%
“…Yet, the risk of contracting SARS-CoV-2 does not depend on the individual's nutritional status but on the degree of contact with the pathogen. Whether the coronavirus exposure develops into a true infection might contrariwise depend on the individual's first-line abilities, and, regrettably, malnutrition is a common occurrence that afflicts many older adults in China (47) and Italy (48), both having been heavily afflicted by the highest number of deaths. It is clear that the segment of population most at risk of SARS-CoV-2 infection is the elderly, with frailty (49) and older age (50) being well-known predictors of a negative outcome in acute care settings.…”
Section: Resultsmentioning
confidence: 99%
“…In all care settings, it is important to characterize the determinants of malnutrition, as intervention strategies may need to be more general and focused on the improvement of structural characteristics of the hospital/nursing home facility as well as on the specific rehabilitation process of the individual patient. Although several studies have been conducted in Italy on the prevalence of malnutrition in nursing homes [ 16 , 17 ], few data are available concerning risk factors for poor nutritional status in older institutionalized adults.…”
Section: Introductionmentioning
confidence: 99%